2017
DOI: 10.1007/s13566-017-0328-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and toxicity of conventional radiotherapy treatment for painful spinal metastases: a detailed course of side effects after opposing fields versus a single posterior field technique

Abstract: BackgroundConventional radiotherapy for painful spinal metastases can be delivered with a single posterior-anterior (PA) or two opposed anterior-posterior (APPA) fields. We studied the effectiveness and toxicity of both techniques and studied whether treatment technique was predictive for abdominal and skin toxicity.Patients and methodsWithin the Dutch Bone Metastasis Study, 343 patients received 8 Gray in a single fraction or 24 Gray in six fractions for painful spinal metastases. Treatment technique was not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…13 The reported incidence of adverse events with radiotherapy is similar, yet the adverse event profile is substantially less severe in comparison with surgical adverse events. 14 In the current study, posttreatment adverse events were reported in 33% of the surgically treated patients and in 12% of the radiotherapy patients. The occurrence of an adverse event, with the exception of the occurrence of an intraoperative adverse event, was in neither of the groups associated with dissatisfaction after treatment.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…13 The reported incidence of adverse events with radiotherapy is similar, yet the adverse event profile is substantially less severe in comparison with surgical adverse events. 14 In the current study, posttreatment adverse events were reported in 33% of the surgically treated patients and in 12% of the radiotherapy patients. The occurrence of an adverse event, with the exception of the occurrence of an intraoperative adverse event, was in neither of the groups associated with dissatisfaction after treatment.…”
Section: Discussionmentioning
confidence: 50%
“…Surgery for spinal metastases is, despite the advances in surgical techniques, often invasive surgery as reflected by reported adverse event rates of up to 76% . The reported incidence of adverse events with radiotherapy is similar, yet the adverse event profile is substantially less severe in comparison with surgical adverse events . In the current study, posttreatment adverse events were reported in 33% of the surgically treated patients and in 12% of the radiotherapy patients.…”
Section: Discussionmentioning
confidence: 52%
“…An optimal radiotherapy regimen palliates symptom with minimal toxicity. In general, the published data regarding toxicity, reveals that treatment was well tolerated [16][17][18].…”
Section: Discussionmentioning
confidence: 98%
“…It is therefore that a combined immune therapy and directed to the EMT, would lead to decrease the robustness of the system and consequently to increase the efficacy in the treatment of tumors in advanced phase. Resistance to therapeutic regimens is a key problem for cancer therapy, as it precludes complete remove of the tumour and enables tumour recurrence, which is one of the main causes of death [10,41] .…”
Section: Discussionmentioning
confidence: 99%